Description of the Molecular and Phenotypic Spectrum of Lesch-Nyhan Disease in Eight Chinese Patients - Li, Lu; Qiao, Xiaohui; Liu, Fei; Wang, Jingjing; Shen, Huijun; Fu, Haidong; Mao, Jian-Hua (Frontiers in Genetics, 2022)
Background Lesch-Nyhan disease (LND) is a rare disorder involving mutations in the HPRT1 gene encoding the enzyme hypoxanthine-guanine phosphoribosyltransferase (HGPRT) that result in hyperuricemia, intellectual disability, dystonic disorder, and compulsive self-mutilation. The purpose of the present study was to characterize the genetic basis of LND and describe its phenotypic heterogeneity by identifying the variation in the HPRT1 gene in a cohort of Chinese LND patients. Results The median age at diagnosis was 20 mo (interquartile range (IQR): 12 to 76 mo), and the initial manifestations were mainly head control weakness and motor development delay. The median age of self-mutilation behavior onset was 17 mo (IQR: 17 to 24 mo), and all patients were required to travel in a wheelchair and fall into the predicament of compulsive self-harm behavior. There were two patients whose blood uric acid levels were normal for their high urinary acid excretion fraction without taking uric acid-lowering drugs. Eight different mutations in the HPRT1 gene were identified among nine independent pedigrees, including four novel mutations [c.299 (exon 3) T>A; loss (exon: 6) 84 bp; c.277_281delATTGCp; c.468_470delGAT]. The mutation sites were mainly concentrated in exon 3, and truncating mutations (including frameshift mutations and nonsense mutations) were the most common mutation types (5/8, 62.5%). Conclusions The present study described the phenotypic and molecular spectrum of LND in nine Chinese families, including four novel mutations, which expands our understanding of LND.